Sort by

- Relevance
- |Time

**LHS**= xy + xy' = x(y + y') ..........distributive law = x(1) = x RHS = (x+y)(x+y' ) = x+(yy') ...........distributive law = x+(0) .............complement law = x**LHS**= RHS1 Answers · Science & Mathematics · 03/08/2019

...x = c/d Then x = (c/d) - (a/b) RHS is clearly rational while

**LHS**is irrational. This is a contradiction. Hence the sum must...4 Answers · Science & Mathematics · 03/08/2019

... the given P(t) and showing that it equals the

**LHS**. Or you can find the solution by solving the DE this way: ...1 Answers · Science & Mathematics · 14/02/2019

...75707>pi-x>2.52611 {the principal values} Check: take x=0.609

**LHS**=ln[4-2(0.32723837...)]=1.20762311.. RHS=ln[3+0.32723837...]=1.20214264.. =>**LHS**...3 Answers · Science & Mathematics · 11/02/2019

It is the distributive law, but you have to *prove* that by showing the

**LHS**is a subset of the RHS and the RHS is a subset of the**LHS**and therefore**LHS**= RHS. Check the link below.1 Answers · Science & Mathematics · 06/02/2019

... by 5^2 each side to get 5^(b-1)*5^2 = 2 * 5^2. Simplify

**LHS**to get 5^(b-1 + 2) = 2 * 5^2 5^(b+1) = 2 * 5^2 U can compute the ...3 Answers · Science & Mathematics · 11/12/2018

...prove that csc(x) - sin(x) = cot(x) * cos(x), we begin evaluating from the

**LHS**to show that it's equal to the RHS, i.e.**LHS**: csc(x) - sin(x...8 Answers · Science & Mathematics · 05/12/2018

(x+8)/4 - 1 = x/3 multiply by 4 x+8 - 4 = 4x/3 combine like terms on

**LHS**x + 4 = 4x/3 multiply by 3 3x + 12 = 4x subtract 3x x = 122 Answers · Science & Mathematics · 09/10/2018

**LHS**= (cos 2x - cos x) / (cos x - 1) = [ 2cos^2(x) - 1 - cos(x)]/[cos(x) - 1...3 Answers · Science & Mathematics · 06/06/2018

**LHS**= -(**LHS**) --->**LHS**+ (**LHS**) = 0 2(**LHS**) = 0 or**LHS**= 05 Answers · Science & Mathematics · 02/05/2018